Impacts of patch-burn grazing on livestock and vegetation in the tallgrass prairie - Rensink, Cade Brion (Kansas State University, 2009)
Patch-burn grazing is a relatively new concept in terms of rangeland management. While numerous benefits have been associated with this system, in the tallgrass prairie of Kansas, cattle production and sustainability of rangeland are critical. In 2006, 253 ha at the KSU Bressner Range Research Unit in Woodson County, Kansas were subjected to spring patch-burn grazing (using one-third portions) and traditional full-burn grazing. Each treatment within the split-block design was replicated four times for 3 years. The objectives were to evaluate whether livestock performance would be compromised under this grazing system, to monitor the health of the rangeland, and to observe the usefulness of this tool as a potential control of the invasive plant sericea lespedeza [Lespedeza cuneata (Dumont) G. Don]. In regards to cattle performance, burn treatments had no significant difference in average daily gain (p≥0.10) in any of the 3 years. On average, cattle utilized 61% of the current year’s forage production in patch-burned portions, which was higher (p≤0.10) than that of unburned (30%) and full-burn (41%) portions. Results of the botanical composition show forb and woody plant composition did not differ between treatments, however differences (p≤0.10) were present in grass composition. Total annual grasses increased 19.1 percentage units under patch-burn and 2.1 units under full-burn, while total perennial grasses decreased 18.4 and 1.1 units, respectively. When evaluated by treatment area (one-third portion), results indicated that the 3-year cycle did allow enough time for recovery. At 2 years after treatment (2-YAT), no significant difference in composition(p≥0.10) was present between initial patch-burn portions and the full-burn pastures. Finally, in only 1 year of the study did cattle statistically consume a greater percentage of sericea lespedeza plants (p≤0.10) in the patch-burned portions (92%) than in full-burned pastures (35%). Biomass utilization did not differ (p≥0.10) between burn treatments. Surprisingly, there was a trend for the number of plants in the sampled areas of the patch-burn portions to decrease throughout the cycle. However, at the conclusion of the 3-year cycle, sericea densities did not differ(p≥0.10) between treatments. Patch-burn grazing shows promise as a potential management tool for Kansas land managers.
Keywords: Rangeland management; Patch-burn grazing; Livestock performance; Grazing distribution; Botanical composition; Sericea lespedeza; Agriculture, Agronomy (0285); Agriculture, Range Management (0777)